Maturity, Bond Rating And Debt To Equity Ratio Effect On Yield To Maturity - Siregar, Ifan Wicaksana; Suci Pratiwi, Indah (Universitas Pendidikan Indonesia, 2020)
This study aims to examine the effect of maturity, bond rating, and debt to equity ratio on yield to maturity. The object of this research is corporate bonds listed on the Indonesia Stock Exchange with the period from 2014-2018. The research sample was selected using purposive sampling. This study uses multiple linear regression analysis techniques. The results showed maturity and debt to equity had no effect on yield to maturity, while bond ratings had a negative effect on yield to maturity. The results of this study prove that bond rating information is useful for investors in determining which bonds to buy. The results of this study provide information that investors do not acquire maturity and debt to equity the primary factors in determining bonds. However, it is expected that investors will use debt to equity as additional consideration for investing in bonds.